PENYERDEHANAAN SURAT SUARA PEMILU DALAM PRESFEKTIF SISTEM PEMILU DAN PEMERINTAHAN PRESIDENSIAL - Sahran Raden (Qaumiyyah: Jurnal Hukum Tata Negara, 2021)
This paper aims to analyze the ideas and policy proposals for simplification of ballot papers implemented in the 2024 simultaneous elections. This simplification of ballots is carried out in an effort to make it easier for voters to vote on voting day in the simultaneous elections, especially in getting to know election participants and their candidates in the right way and legitimate. In addition, simplification of ballot papers makes it easier for election organizers in the process of vote counting accuracy. The design of the electoral ballot must always be relevant to the electoral system and the context of a country's system of government. How is the design of election ballots in the context of the electoral system and the presidential government system adopted in Indonesia. Abstrak Tulisan ini bertujuan untuk menganalisis gagasan dan usulan kebijakan penyederhaan surat suara yang dilaksanakan dalam pemilu serentak 2024. Penyederhanaan surat suara ini dilakukan dalam upaya untuk memudahkan pemilih dalam memilih saat hari pemungutan suara pada pemilu serentak terutama dalam mengenal peserta pemilu dan kandidatnya dengan cara yang benar dan sah. Selain itu penyederhaan surat suara memberikan kemudahan bagi penyelenggara pemilu dalam proses akurasi penghitungan suara. Desain surat suara pemilu harus selalu relevan dengan sistem pemilu dan konteks sistem pemerintahan suatu negara. Bagaimana desain surat suara pemilu dalam konteks sistem pemilu dan sistem pemerintahan Presidensial yang dianut di Indonesia.